Application of SeDeM Expert System in the development of novel directly compressible co-processed excipients via co-processing - Ilyasu Salim; Adeniji Kehinde Olowosulu; Abdulrahman Abdulsamad; Mahmud Sani Gwarzo; Garba Mohammed Khalid; Naimatu Tijjani Ahmad; Florence Egbomonjiade Eichie; Fatima Shuaibu Kurfi (SpringerOpen, 2021)
Abstract Background Computer-aided formulation design is gaining fantastic attention in chemical engineering of high functionality pharmaceutical materials for dosage form manufacture. To accelerate development of novel formulations in a quality-by-design perspective, SeDeM Expert System preformulation algorithm was developed as a tool for the design of solid drug delivery systems and for prediction of direct compression manufacturability of solid formulations. This research aims to integrate SeDeM Expert System into particle engineering design space of co-processing of solid excipients to develop novel composites with optimum direct compression propensity, using corn starch and microcrystalline cellulose powders as model primary excipients. Result The data and information generated from the expert system have elucidated the bulk-level characteristics of the primary excipients, enabled computation of the optimum co-processing ratio of the ingredients, and validated the impact of co-processing on material functionality. The experimental flowability (7.78±0.17), compressibility functions (5.16±0.14), parameter profile (0.92), and parametric profile index (6.72±0.27) of the engineered composites, were within the acceptable thresholds. With a reliability constant of 0.961, the net direct compression propensity of the composites expressed as Good Compression Index (6.46±0.26) was superior to that of the primary excipients, but comparable to reference co-processed materials, StarLac® (6.44±0.14) and MicroceLac®100 (6.58±0.03). Conclusion Application of SeDeM Expert System in particle engineering via co-processing has provided an accelerated upstream proactive mechanism for designing directly compressible co-processed excipients in a quality-by-design fashion. A four-stage systematic methodology of co-processing of solid excipients was postulated. Stage I entails the characterization of CMAs of both defective and corrective excipients, and elucidation of their physicomechanical limitations using SeDeM diagrams. Stage II involves computation of loading capacity of the corrective excipient using dilution potential equation. Stage III entails the selection of co-processing technique based on desired Critical Material Attributes as revealed by the information obtained from Stage I. Stage IV evaluates the impact of co-processing by monitoring the critical behavior of the engineered composites with a decision on either to accept or reject the product.